Variasi Frekuensi pada Electric Rotary Table Berbasis Inverter Guna Menurunkan Cycle Time dan Cacat Produk pada Pengelasan Pipa Kapiler - Nailul Ulum, Muhammad Showi; Prasetyo, Nanang Budi; Sai'in, Ali; Su'udy, Ahmad Hamim; Hamid, Abdul; Purnomo, Dwi (Mechanical Engineering Department - Semarang State Polytechnic, 2023)
Abstract Cycle Time is a matter that must be considered in production time, a good Cycle Time will support the targets that must be met, even if Cycle Time decreases, production will also increase and company turnover will also Increase. In the case study of PT Arisamandiri Pratama, one of its productions is in the form of AC parts, namely capillary pipes which still use a manual rotating table to rotate the pipe to be welded so that it is unable to reach the target of 800 parts / hour with an average Not Good product of 93 parts / day. The design of an inverter-based electric rotary table can reduce cycle time, but how much frequency will affect the results of a welding, not that the faster the welding process the better, the faster the welding will affect the vibration of the table machine which will have an impact on the welding results. By experiment the inverter frequency setting is expected to get a frequency value with maximum speed but no vibration on the rotation table, the frequency used is between 700 Hz to 1500 Hz with an interval of 100 Hz. The experimental results show that the best frequency is 1000 Hz, with a rotation speed of 16 rpm with a production capacity of 935 parts / hour with Not Good products of 59 parts / day or a decrease in Not Good products by 42.1% per day